o

To solve the equation \( \frac{b - 5}{-2b + 5} = \frac{50}{b^2 - 25} \), let's start by rewriting the equation:
\[
\frac{b - 5}{-2b + 5} = \frac{50}{b^2 - 25}
\]

### Step 1: Factor the Denominator

We notice that \( b^2 - 25 \) can be factored since it's a difference of squares:

\[
b^2 - 25 = (b - 5)(b + 5)
\]

Now re-write our equation:

\[
\frac{b - 5}{-2b + 5} = \frac{50}{(b - 5)(b + 5)}
\]

### Step 2: Cross-multiply

Next, we can cross-multiply to eliminate the fractions:

\[
(b - 5)(b - 5) = 50(-2b + 5)
\]

### Step 3: Expand both sides

The left side becomes \( (b - 5)^2 \):

\[
(b - 5)^2 = b^2 - 10b + 25
\]

The right side expands as follows:

\[
50(-2b + 5) = -100b + 250
\]

### Step 4: Set the equation

Now we set the two expressions equal to each other:

\[
b^2 - 10b + 25 = -100b + 250
\]

### Step 5: Move all terms to one side

Now, combine like terms by moving everything to one side of the equation:

\[
b^2 - 10b + 25 + 100b - 250 = 0
\]

This simplifies to:

\[
b^2 + 90b - 225 = 0
\]

### Step 6: Solve the quadratic equation

Now, we can apply the quadratic formula \( b = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \), where:

- \( A = 1 \)
- \( B = 90 \)
- \( C = -225 \)

Let's calculate the discriminant:

\[
B^2 - 4AC = 90^2 - 4(1)(-225) = 8100 + 900 = 9000
\]

Now, apply the quadratic formula:

\[
b = \frac{-90 \pm \sqrt{9000}}{2}
\]

The square root of \( 9000 \) can be simplified:

\[
\sqrt{9000} = \sqrt{90^2 \times 10} = 90 \sqrt{10}
\]

So, we have:

\[
b = \frac{-90 \pm 90 \sqrt{10}}{2} = -45 \pm 45 \sqrt{10}
\]

### Step 7: Final Result

Therefore, the solutions for \( b \) are:

\[
b = -45 + 45\sqrt{10} \, \text{and} \, b = -45 - 45\sqrt{10}
\]

This completes the solution of the equation.
(remove frac pm sqrt / } { \ )

1 answer

To solve the equation \( \frac{b - 5}{-2b + 5} = \frac{50}{b^2 - 25} \), let's start by rewriting the equation properly:

\[ \frac{b - 5}{-2b + 5} = \frac{50}{b^2 - 25} \]

Step 1: Factor the Denominator

We notice that \( b^2 - 25 \) can be factored, as it is a difference of squares:

\[ b^2 - 25 = (b - 5)(b + 5) \]

Now we can re-write our equation:

\[ \frac{b - 5}{-2b + 5} = \frac{50}{(b - 5)(b + 5)} \]

Step 2: Cross-multiply

Next, we can cross-multiply to eliminate the fractions:

\[ (b - 5)(b - 5) = 50(-2b + 5) \]

Step 3: Expand both sides

The left side simplifies to \( (b - 5)^2 \):

\[ (b - 5)^2 = b^2 - 10b + 25 \]

The right side expands as follows:

\[ 50(-2b + 5) = -100b + 250 \]

Step 4: Set the equation

Now we set the two sides equal to each other:

\[ b^2 - 10b + 25 = -100b + 250 \]

Step 5: Move all terms to one side

Bringing all terms to one side gives:

\[ b^2 - 10b + 25 + 100b - 250 = 0 \]

This simplifies to:

\[ b^2 + 90b - 225 = 0 \]

Step 6: Solve the quadratic equation

Next, we use the quadratic formula \( b = \frac{-B \pm \sqrt{B^2 - 4AC}}{2A} \), where:

  • \( A = 1 \)
  • \( B = 90 \)
  • \( C = -225 \)

Calculating the discriminant:

\[ B^2 - 4AC = 90^2 - 4(1)(-225) = 8100 + 900 = 9000 \]

Now we apply the quadratic formula:

\[ b = \frac{-90 \pm \sqrt{9000}}{2} \]

The square root of \( 9000 \) can be simplified:

\[ \sqrt{9000} = \sqrt{90^2 \cdot 10} = 90\sqrt{10} \]

Therefore, substituting back into the formula gives us:

\[ b = \frac{-90 \pm 90\sqrt{10}}{2} = -45 \pm 45\sqrt{10} \]

Step 7: Final Result

Thus, the solutions for \( b \) are:

\[ b = -45 + 45\sqrt{10} \quad \text{and} \quad b = -45 - 45\sqrt{10} \]

These represent the complete solution to the equation.

Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. oTo solve the equation \( \frac{b - 5}{-2b + 5} = \frac{50}{b^2 - 25} \), let's start by rewriting the equation: \[ \frac{b -
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions